Heterogeneity of discontinuous carbon fibre composites: Damage initiation captured by Digital Image Correlation. (January 2015) - Johanson, K.; Harper, L.T.; Johnson, M.S.; Warrior, N.A.
Abstract: This paper aims to identify architectural features which lead to damage initiation and failure in discontinuous carbon fibre composites formed from randomly orientated bundles. A novel multi-camera Digital Image Correlation system was used to simultaneously view strain fields from opposing surfaces of coupons, in order to map progression of failure. The highest strain concentrations were found to occur when the ends of fibre bundles aligned in the direction of loading coincided with underlying transverse bundles. The failure plane was observed to grow between a number of strain concentrations at critical features, coalescing sites of damage to create the final fracture surface. Although potential failure sites can be detected at low global strains in the form of strain concentrations, the strain field observed at low applied loads cannot be extrapolated to reliably predict final failure.